2011
DOI: 10.1002/ieam.105
|View full text |Cite
|
Sign up to set email alerts
|

Framework for traits‐based assessment in ecotoxicology

Abstract: A key challenge in ecotoxicology is to assess the potential risks of chemicals to the wide range of species in the environment on the basis of laboratory toxicity data derived from a limited number of species. These species are then assumed to be suitable surrogates for a wider class of related taxa. For example, Daphnia spp. are used as the indicator species for freshwater aquatic invertebrates. Extrapolation from these datasets to natural communities poses a challenge because the extent to which test species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
151
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(156 citation statements)
references
References 91 publications
3
151
1
Order By: Relevance
“…For example, trait-based approaches can provide a mechanistic understanding of the success of certain organisms under given environmental conditions and to relate individual-or population-level phenotypic changes to higher level changes in structure and functioning (McGill et al 2006;Litchman et al 2007;Suding et al 2008;Reiss et al 2009;Edwards et al 2013). Trait-based approaches are also being used in ecotoxicology to improve the description of ecological responses to pollutants (such as pesticides) and to extrapolate between different species or populations using traits related to the vulnerability to stressors (Rubach et al 2011;Ippolito et al 2012). In this study we focused on individual phenotypic traits, associated with the morphology and physiology of organisms and therefore their individual fitness (Fig.…”
Section: Trait-based Response and Effect Frameworkmentioning
confidence: 99%
“…For example, trait-based approaches can provide a mechanistic understanding of the success of certain organisms under given environmental conditions and to relate individual-or population-level phenotypic changes to higher level changes in structure and functioning (McGill et al 2006;Litchman et al 2007;Suding et al 2008;Reiss et al 2009;Edwards et al 2013). Trait-based approaches are also being used in ecotoxicology to improve the description of ecological responses to pollutants (such as pesticides) and to extrapolate between different species or populations using traits related to the vulnerability to stressors (Rubach et al 2011;Ippolito et al 2012). In this study we focused on individual phenotypic traits, associated with the morphology and physiology of organisms and therefore their individual fitness (Fig.…”
Section: Trait-based Response and Effect Frameworkmentioning
confidence: 99%
“…The first breakout group developed a framework for incorporating species traits in ecotoxicology and the ERA of chemicals (Rubach et al 2011). For this they adapted the vulnerability model of Van Straalen (1994), which distinguishes external exposure, intrinsic sensitivity, and population sustainability as determinants of population vulnerability.…”
mentioning
confidence: 99%
“…In contrast, the prawn is an epibenthic crustacean and is fully submerged throughout the exposure, using gill respiration (Liu et al 2005). It is suggested that respiration strategy and locomotion mode may largely influence the bioaccumulation of contaminants in aquatic species (Borgå et al 2004;Rubach et al 2011), although there is no such data on TBBP-A. Comparing BAFs between the prey fish species and the predator fish, mud carp (two group t test, p = 0.003) and crucian carp (two group t test, p = 0.001) showed significantly higher BAFs than northern snakehead.…”
Section: Bioaccumulation Potential and Species-specific Accumulationmentioning
confidence: 99%